Cranial hemihypertrophy and neurodevelopmental prognosis. Issue 3 (March 1990) - Dean, J C; Cole, G F; Appleton, R E; Burn, J; Roberts, S A; Donnai, D
Abstract : Three cases of congenital cranial hemihypertrophy are described. CT or ultrasound scans showed unilateral cerebral enlargement with dilatation of the ipsilateral ventricle. Seizures occurred in two patients and the neurodevelopmental outlook appears poor. These patients represent a poor prognosis subgroup of the congenital hemihypertrophies.